Search for supersymmetry in final states with missing transverse momentum and charm-tagged jets using 139 fb−1 of proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk (Journal of high energy physics, 2025)
The paper presents a search for supersymmetric particles produced in proton-proton collisions at √s = 13 TeV and decaying into final states with missing transverse momentum and jets originating from charm quarks. The data were taken with the ATLAS detector at the Large Hadron Collider at CERN from 2015 to 2018 and correspond to an integrated luminosity of 139 fb−1. No significant excess of events over the expected Standard Model background expectation is observed in optimized signal regions, and limits are set on the production cross-sections of the supersymmetric particles. Pair production of charm squarks or top squarks, each decaying into a charm quark and the lightest supersymmetric particle χ̃01, is excluded at 95% confidence level for squarks with masses up to 900 GeV for scenarios where the mass of χ̃01 is below 50 GeV. Additionally, the production of leptoquarks with masses up to 900 GeV is excluded for the scenario where up-type leptoquarks decay into a charm quark and a neutrino. Model-independent limits on cross-sections and event yields for processes beyond the Standard Model are also reported.
Gesehen am 09.01.2026
The ATLAS collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, D.F. Rassloff, L. Sanfilippo, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, M. Wessels, J. Zinsser [und viele weitere]